Paper towns - Green, John, 1977- (London : Bloomsbury Publishing PLC, 2015)
One month before graduating from his Central Florida high school, Quentin "Q" Jacobsen basks in the predictable boringness of his life until the beautiful and exciting Margo Roth Spiegelman, Q's neighbor and classmate, takes him on a midnight adventure and then mysteriously disappears.
Booklist starred.
Library Media Connection starred.
School Library Journal starred.
Young Adult
Keywords: Missing persons -- Juvenile fiction; Coming of age -- Fiction; Missing persons -- Fiction; Mystery and detective stories; Bildungsromans; Missing persons -- Fiction; Mystery fiction; Florida -- Juvenile fiction; Florida -- Fiction; Florida -- Fiction; Bildungsromans; Mystery fiction